Exploring movies for language learning / Norwati Roslim ... [et al.] - Roslim, Norwati; Azizul, Aini Faridah; Nimehchisalem, Vahid; Tew Abdullah, Muhammad Hakimi (Akademi Pengajian Bahasa, 2021)
The increasing importance of using movies to enhance second language teaching and learning have been addressed by researchers and educators. Few scholarly studies have effortlessly put forward significant findings on using movies in the area of theoretical bases, pedagogical aspects and learners’ perspectives, however, more studies need to be explored further as proposed by many scholars in their suggested future research. Hence, this study aims to investigate perceptions and experiences among university undergraduate students in exploring English language movies of their own choice for their oral commentary presentations. A corpus of English movies selected by students was used to assist students in their presentations. 77 university undergraduates took part in the study and the data was collected through an online survey which consisted of a three-section questionnaire: demographic profile, learners’ perceptions and learners’ experiences. The data were analysed descriptively using SPSS version 20. The results revealed that using movies has helped students mainly, in improving their oral skills, vocabulary, interest and motivation as well as decreasing their anxiety and tension. It is hoped that this study could add to the body of knowledge and benefit educators and instructors on using movies for language teaching and learning.